2019
DOI: 10.1074/jbc.ra119.007755
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 is essential for maintaining functional β-cell mass during diabetes through inhibiting both FOXO1 and SOX6 pathways

Abstract: The initiation and development of diabetes are mainly ascribed to the loss of functional ␤-cells. Therapies designed to regenerate ␤-cells provide great potential for controlling glucose levels and thereby preventing the devastating complications associated with diabetes. This requires detailed knowledge of the molecular events and underlying mechanisms in this disorder. Here, we report that expression of microRNA-223 (miR-223) is up-regulated in islets from diabetic mice and humans, as well as in murine Min6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…Previous studies have shown that miR-223 could be involved in a variety of biological activities such as tumor suppression or metabolic disease [22][23][24][25][26][27]. Furthermore, it is reported that miR-223 knockout mice exhibit impaired glucose tolerance and IR [20]. Here, in vitro studies validated that uc.333 can suppress the level of miR-223 in HepG2 cells.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that miR-223 could be involved in a variety of biological activities such as tumor suppression or metabolic disease [22][23][24][25][26][27]. Furthermore, it is reported that miR-223 knockout mice exhibit impaired glucose tolerance and IR [20]. Here, in vitro studies validated that uc.333 can suppress the level of miR-223 in HepG2 cells.…”
Section: Discussionsupporting
confidence: 59%
“…He et al (38) demonstrated that in human osteosarcoma, mir-374a enhanced cell growth by inhibiting downstream FOXO1 signaling, which is consistent with the results of the current study in human ovarian cancer cells. Furthermore, p27 is a CDK inhibitor that has a negative regulatory effect on proliferation and is a downstream target of FOXO1; consequently, FOXO1 inhibits cell proliferation by upregulating p27 (39)(40)(41)(42). The Bim protein belongs to the Bcl-2 protein family and exerts a pro-apoptotic effect on cells (43,44); previous studies have confirmed that FOXO1 regulates cell apoptosis through its downstream targets, including Bim (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these findings, miR-223 was discovered to be downregulated in peripheral blood. Interestingly, it was found to be upregulated in the pancreatic islets of T2DM patients, which can likely be explained by a feedback mechanism caused by high blood glucose [82]. Also, miR-223 increases the expression of GLUT4 protein to improve glucose intake, so that insulin resistance is mitigated [83].…”
Section: Mir-223mentioning
confidence: 99%